P73 A prospective multifaceted evaluation of the impact of Kaftrio in children with cystic fibrosis. (11th November 2022) - Gajaweera, H; Day, M; Connett, G; Cannell, C; Legg, J
Abstract : Introduction: Kaftrio (Elexacaftor-Tezacaftor-Ivacaftor) is a recently introduced CFTR modulator to treat people with Cystic fibrosis (CF) who have at least one copy of the F508del mutation. We have evaluated the wider efficacy of this treatment using the Cystic Fibrosis Questionnaire-Revised (CFQ-R), Warwick-Edinburgh Mental Wellbeing Score (WEMWBS) and a Pancreatic Exocrine Insufficiency Questionnaire (PEI-Q) in children aged over 12 years attending the Southampton Children's Hospital CF service. Methods: Questionnaires were completed before and 6–9 months after starting Kaftrio. The CFQ-R data were obtained using age-appropriate tools for children aged 12–13 years and over 14 years respectively. Data were obtained as a component of routine clinical care either face to face or through semi-structured telephone consultations. Data from participants who completed both sets of questionnaires were analysed using Wilcoxon signed ranked test. Results: Twenty-seven children (11 aged 12–13 years, 16 aged over 14 years) completed pre-treatment questionnaires and 22 (7 aged 12–13 years, 15 aged over 14 years) completed post-treatment questionnaires. 16 participants completed both sets of questionnaires. All participants were pancreatic insufficient. There was a trend towards improvement in all CFQ-R domains and this was significant for respiratory symptoms. There were significant improvements in abdominal symptoms and total summary scores for GI outcomes as measured by the PEI-Q suggesting improvements in symptoms due to pancreatic insufficiency. There was no change in WEMWBS scores. Conclusion: The assessment tools used in this study usefully identified improvements in gastrointestinal and respiratory symptoms. The lack of change in indices of mental well-being is probably a result of relatively good mental health in this age group prior to CFTR modulator treatment and may have been influenced by the impact of the COVID pandemic during which this study was conducted.